A multi-scale model for global buckling and local wrinkling interaction with application to sandwich beams. (August 2021) - Mhada, Khadija; Bourihane, Oussama
Abstract: In this work, we present a new 2D Reduced model capable of taking into account the coupling between local instabilities and global buckling which occur in sandwich structures. To establish this model, we use a multi-scale approach based on the technique of Fourier series with slowly varying coefficients which allows transforming a 2D sandwich model into 2D Reduced model, of which only the envelope of instability is numerically evaluated. It is like the Ginzburg–Landau envelope equation, but it provides the post buckling behavior and takes into account the coupling between global and local instabilities. The proposed model is validated by comparison with the 2D Complete model and the analytical solution. The non-linear system is solved by the Asymptotic Numerical Method (ANM), which is an efficient, robust and accurate continuation method for solving non-linear systems.